Qualitative and Quantitative Assessment of the Soil Organic Substances Present in the Forest Litter of Chakrata Himalayas (Uttar Pradesh) - Singhal, R. M.; Kumar, Promod (Indian Forester, 1988)
The biochemical composition of the forest litter, before and after its incorporation in to the mineral soil was studied in certain forest areas of Chakrata Himalayas (U.P). It was found that although the humus type was 'Orthirhizomull' under all the species under investigation viz. Cedrus devdara, Pinus wallichiana, Pinus roxburghii, Picea smithiana and Abies pindrow its composition, in terms of recognisable organic substances was different from species to species. The litter under P. roxburghii and P. wallichiana was richer in cellulose and hemicellulose content while others in fats, waxes, oils and water soluble polysaccharides contents. Conversion of these substances into high molecular weight compounds was on account of decomposition and synthesis by the primary and secondary flora.